2016
DOI: 10.3348/kjr.2016.17.6.827
|View full text |Cite
|
Sign up to set email alerts
|

Structural MR Imaging in the Diagnosis of Alzheimer's Disease and Other Neurodegenerative Dementia: Current Imaging Approach and Future Perspectives

Abstract: With the rise of aging population, clinical concern and research attention has shifted towards neuroimaging of dementia. The advent of 3T, magnetic resonance imaging (MRI) has permitted the anatomical imaging of neurodegenerative disease, specifically dementia, with improved resolution. Furthermore, more powerful techniques such as diffusion tensor imaging, quantitative susceptibility mapping, and magnetic transfer imaging have successfully emerged for the detection of micro-structural abnormalities. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 150 publications
1
65
0
9
Order By: Relevance
“…). Thus, estimates of the amount of iron deposition in the drain can be used for evaluating the presence and progression of AD (Park and Moon ). Studies have found increased levels of iron in the putamen, pulvinar thalamus, red nucleus, hippocampus, and the temporal cortex of AD patients but the clinical consequences of these findings remain unknown (Langkammer et al .…”
Section: Iron Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…). Thus, estimates of the amount of iron deposition in the drain can be used for evaluating the presence and progression of AD (Park and Moon ). Studies have found increased levels of iron in the putamen, pulvinar thalamus, red nucleus, hippocampus, and the temporal cortex of AD patients but the clinical consequences of these findings remain unknown (Langkammer et al .…”
Section: Iron Imagingmentioning
confidence: 99%
“…Pathological studies of patients with AD show plaques, neurofibrillary tangles, and neurons that contain high amount of iron, which is indicative of disruption in iron homeostasis in the brain . Thus, estimates of the amount of iron deposition in the drain can be used for evaluating the presence and progression of AD (Park and Moon 2016). Studies have found increased levels of iron in the putamen, pulvinar thalamus, red nucleus, hippocampus, and the temporal cortex of AD patients but the clinical consequences of these findings remain unknown (Langkammer et al 2014).…”
Section: Iron Imagingmentioning
confidence: 99%
“…Structural imaging procedures have been successful in AD diagnostics (Chetelat and Baron, 2003;Frisoni, Fox, Jack, Scheltens, & Thompson, 2010;Park and Moon, 2016;Teipel et al, 2013). This is due to the fact that structural atrophy mirrors patterns of the characteristic regional pathology of this condition (Jack, Petersen, O'brien, & Tangalos, 1992;Jack et al, 1997;Scheltens et al, 1992).…”
Section: Oscarmentioning
confidence: 99%
“…In recent years, considerable efforts have been made to identify neuroimaging biomarkers, with the aim of providing objective measures of disease pathology before symptom onset (Varghese, Sheelakumari, James, & Mathuranath, 2013). Most of this work has been carried out using structural Magnetic Resonance Imaging (MRI) (Park & Moon, 2016). Estimates of the sensitivity and specificity of MRI markers in detecting AD range from 82-89% and 86-97%, respectively (see Beheshti, Demirel, Matsuda, & Initiative, 2017, for a summary of recent studies).…”
Section: Introductionmentioning
confidence: 99%